Limited water access is associated with food insecurity and diarrheal episodes among children suffering from moderate acute malnutrition in Far-North Cameroon. (16th December 2021) - Nounkeu, Carole Debora; Teta, Ismael; Dharod, Jigna Morarji; Saha Foudjo, Brice Ulrich; Ntentie, Francoise Raissa; Boris, Azantsa Kingue; Georges, Nguefack-Tsague; Oben, Julius
Abstract: To gain further understanding of the interlinkages between poor water access, household food insecurity, and undernutrition among children, this study used a cross-sectional design with 474 female caretakers of children suffering from moderate acute malnutrition (MAM) to explore the relationship between limited access to water and diarrheal diseases among children, aged <5 years, experiencing MAM. The mean age of the caretakers was 28.50±6.88 years and that of their MAM children (sex ratio=0.7) was 17.79±9.59 months. The participants reported spending an average of 19.29±15.69 min for one trip to fetch water. A negative correlation was found between mean time spent fetching drinking water and hygiene and handwashing score ( r =−0.141, p =0.003). Furthermore, the more severe the food insecurity status of a household, the farther the family member likely had to go to fetch drinking water [ F (2, 444)=8.64, p ≤0.001]. Results from binary logistic regression showed that children from households practicing open defecation ( p =0.008) and/or having inadequate hygiene practices ( p =0.004) had increased odds of developing diarrhea. Therefore, ameliorating water access in households with MAM children could contribute to improvements in hygiene and sanitation attitudes with a subsequent increase in the effectiveness of nutrition interventions aiming at reducing acute malnutrition among children. HIGHLIGHTS: Wasting is a huge public health emergency in sub-Saharan Africa with 6.9% of children aged <5 years being affected. The existence of relationships between the different forms of undernutrition and water, sanitation, and hygiene may contribute toward the persistency of children's poor nutritional status. Children from households practicing open defecation or with poor hygiene practices have increased odds of having diarrhea.